The Association Between Menstrual Hygiene Practices and Pruritus vulvae Among Female Students at MTS Siti Khadijah Sindangwangi, Majalengka, Indonesia (2020) - Muhidin Muhidin; Teten Rustendi; Muslimin Muslimin; Rokhmatul Hikhmat (Green Publisher Indonesia, 2026)
Menstrual hygiene practices are essential to be implemented as part of efforts to prevent and control infections, prevent skin damage, enhance comfort, and maintain personal hygiene. This study aimed to determine the association between menstrual hygiene practices and the incidence of Pruritus vulvae among female students at MTs Siti Khadijah Sindangwangi, Majalengka, in 2020. This study employed a quantitative analytical design with a cross-sectional approach. The independent variable was menstrual hygiene practices, while the dependent variable was Pruritus vulvae. The study population consisted of 74 female students who had experienced menstruation at MTs Siti Khadijah Sindangwangi, Majalengka, in 2020, with a sample of 62 students selected using simple random sampling. Data were collected using a questionnaire and processed through editing, coding, data entry, and tabulation. Statistical analysis was performed using the Spearman rank correlation test. The results showed that 30 respondents (48.4%) had good menstrual hygiene practices, and 37 respondents (59.7%) experienced moderate Pruritus vulvae. The Spearman rank test revealed a significant result (p = 0.000 < α = 0.05), indicating that the alternative hypothesis was accepted. This finding demonstrates a significant association between menstrual hygiene practices and the incidence of Pruritus vulvae among female students.